Determinants of Trade Openness in Sudan: An Empirical Investigation (1970-2007) - Saber, Safiat Ali (Gezira Journal of Economic and Social Sciences; مجلد 1 عدد 1 (2010), 2010)
The purpose of this paper is to investigate the determinants of trade openness in Sudan during the period 1970-2007 using Ordinary Least Square (OLS) technique. Data were obtained from different sources, including: the annual reports of the Central Bank of Sudan, Ministry of Finance and National Economy, and Central Bureau of Statistics. The population size (P), real per capita GDP (Y), real exchange rate (E) and dummy variable of peace (D) were found to be the determinants of trade openness in Sudan. Among these determinants, real exchange rate and population size turned out to be the most important determinants of trade openness in Sudan during the study period.